THEORETICAL ANALYSIS OF FUSION CROSS-SECTIONS IN LIGHT HALO NUCLEAR SYSTEMS USING QUANTUM MECHANICS - Saddon Omran Ghareeb; Fouad A. Majeed (Proceedings on Engineering Sciences, 2025)
This study presents a theoretical analysis of fusion cross-section (σfus), fusion barrier distribution (Dfus), and fusion probability (Pfus) for nuclear systems involving light halo nuclei such as ⁶He, ¹⁵C, and ¹¹Be interacting with ²⁰⁶Pb and ²⁰⁹Bi. Using quantum mechanical coupled channel (CC) simulations, this research examines the role of breakup channels in influencing fusion dynamics under sub-barrier conditions. The study employs the Woods-Saxon potential with optimized parameters fitted to experimental data, refining fusion barrier predictions. Results indicate that channel coupling significantly enhances fusion probabilities, validating the importance of including breakup effects in theoretical models. The findings contribute to a deeper understanding of nuclear fusion mechanisms in weakly bound systems, with implications for both nuclear physics and astrophysical nucleosynthesis.